British Coercive Diplomacy Under Prime Minister Boris Johnson to Russia as an Effort to Resolve the Russia-Ukraine Conflict - Suhayatmi; Hendra Maujana Saragih (Yayasan Ilomata, 2023)
Russia's military attack on the legal territory of Ukraine is considered to be a serious threat to the national interests of the countries on the European continent. Prior to the military attack which Russia calls a “Special Military Operation” starting on February 24, 2022, various efforts to resolve the conflict have been taken by Europe, the United Nations, and other international relations actors. Britain is one of the countries that is actively pursuing diplomacy to stop Russia's actions, which the West calls an illegal invasion. In carrying out its foreign policy, the UK practices Coercive Diplomacy, namely diplomacy with pressure on Russia. This was marked by an ultimatum accompanied by economic, political and military sanctions against Russia. This study uses a qualitative research method based on secondary data from various credible sources and the conceptual theory put forward by Alexander L. George (1971) as the first initiator of the Concept of Coercive Diplomacy. Therefore, this research raises the research question How does Britain apply British Coercive Diplomacy towards Russia as a Conflict Resolution effort?” and will be answered using the characteristics given by Alexander L. George in the concept of Limited Power in Coercive Diplomacy.